Optimal operation of stand-alone microgrid considering emission issues and demand response program using whale optimization Algorithm - Tahmasebi M.; Pasupuleti J.; Mohamadian F.; Shakeri M.; Guerrero J.M.; Basir Khan M.R.; Nazir M.S.; Safari A.; Bazmohammadi N. (MDPI AG, 2023)
algorithm; alternative energy; emission; energy management; genetic algorithm; optimization